The Implementation of Social Media Marketing on Instagram GWK Cultural Park Bali in Creating Customer Engagement - Dewa Ayu Chyntia Novyanti; Maylanny Christin (Metacommunication: Journal of Communication Studies, 2024)
In the current era of globalization, all human activities have evolved to become completely digital. Social media is one of the uses of technology in the field of communication that is often used by people throughout the world. Not only as a medium for communicating and expressing yourself, social media is now widely used for marketing, or what is often called social media marketing. GWK Cultural Park Bali is one of the tourist destinations that implements social media marketing via Instagram. The aim is to provide information regarding the GWK Cultural Park tourist destination to the audience and to create customer engagement. Therefore, this research aims to determine the implementation of social media marketing on Instagram at GWK Cultural Park Bali in creating customer engagement. The method used in this research is descriptive-qualitative, with data collection through interviews, observation, documentation, and a literature study. The data validity technique uses source triangulation. The results of this research show that GWK Cultural Park has carried out social media marketing through four components (context, communication, collaboration, and connection). However, in its application, GWK Cultural Park is not yet optimal in creating interactive content, so interaction from the audience is still lacking. Therefore, there needs to be optimization so that Instagram followers (@gwkbali) feel engaged with this tourist destination.